Survei Implementasi Kurikulum Merdeka pada Pembelajaran PJOK di SD Se Kabupaten Pasuruan - Luthfi Ahmad Baihaqi; Mu’arifin Mu’arifin (Mutiara Pendidikan dan Olahraga, 2025)
The purpose of this research is to understand and examine the level of understanding and problems faced by teachers towards the implementation of the independent curriculum in physical education learning. The population of this study is all PJOK subject teachers in Pasuruan Regency and use cluster random sampling. The instruments in this research used questionnaires, interviews and documentation. Data analysis techniques use quantitative and qualitative descriptive techniques. Quantitative analysis is obtained from the results of teachers filling out questionnaires and analyzed using percentage formulas. While qualitative analysis using data reduction, data presentation, and making conclusions. The results of filling out a questionnaire on the level of teacher understanding of the implementation of the independent curriculum in physical education learning in elementary schools in Pasuruan Regency were obtained 75,53% with the category of understanding most. At the planning stage, 76,40% were obtained, the learning implementation stage was 74,74%, the learning assessment was 74,99%, the processing and reporting stage of assessment results was 75,64%, and the reflection and follow-up stage was 75,26%. Furthermore, the problem that becomes difficult is when carrying out learning which leads to strengthening the Pancasila Student Profile. So it can be concluded that the level of teacher understanding of the implementation of the independent curriculum in PJOK learning in junior high schools in Pasuruan Regency results in understanding most of it. And the most difficult problem lies in Pancasila Student Profile.